2005
DOI: 10.1007/s00421-004-1299-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of strength training on musculotendinous stiffness in elderly individuals

Abstract: The present study deals with the question whether 24-week strength training alters neuromechanical properties of plantar flexors in elderly people (73-83 years). The first purpose of the present study was to evaluate the effect of strength training on musculotendinous (MT) stiffness of the triceps surae (TS). The training was performed twice per week and mainly consisted of three series of ten repetitions of calf-rise and leg-press exercises at 75% of the three-repetition maximum. Using quick-release movements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 31 publications
1
11
0
2
Order By: Relevance
“…Furthermore, using two KF positions is common practice in everyday assessment, rehabilitation, conditioning, and strengthening of the distinct TS muscles (del Porto et al, 2010;Magnussen et al, 2009). Despite this underlying knowledge and widespread clinical use, many studies still employ only one KF position for the simultaneous acquisition of EMG normalization values for all three TS muscles, which range from 0°KF to 120°KF (Ball and Scurr, 2010;Ochala et al, 2005;Simoneau et al, 2009). Our results indicate that employing at least two KF angles in standing is more effective and accurate than just using one in standing to determine peak EMG amplitudes of the TS.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, using two KF positions is common practice in everyday assessment, rehabilitation, conditioning, and strengthening of the distinct TS muscles (del Porto et al, 2010;Magnussen et al, 2009). Despite this underlying knowledge and widespread clinical use, many studies still employ only one KF position for the simultaneous acquisition of EMG normalization values for all three TS muscles, which range from 0°KF to 120°KF (Ball and Scurr, 2010;Ochala et al, 2005;Simoneau et al, 2009). Our results indicate that employing at least two KF angles in standing is more effective and accurate than just using one in standing to determine peak EMG amplitudes of the TS.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few experiments have examined the effect of strength training over 14 weeks (Lexell et al 1995;McCartney et al 1996;Ha¨kkinen et al 1998). The authors observed that MVC continuously increases during a 24-week training on knee extensors (Ha¨kkinen et al 1998) and plantar flexors (Ochala et al 2005), or during a 48-week training on elbow flexors and knee extensors (Lexell et al 1995), or during a 96-week training on knee extensors (McCartney et al 1996).…”
Section: Force Production Capacitiesmentioning
confidence: 96%
“…Nevertheless, since during the quick release experiment, MT release occurs against the resistance of the antagonist muscles, MT stiffness could also be influenced by neural adaptations (Lambertz et al 2001;. Thus, the decrease in SI MT values after the strength training among older men and women may also result from a lower co-activation (Ochala et al 2005). Controversial results have already been observed in the literature concerning co-activation values during maximal contractions as an effect of strength training in elderly people (Ha¨kkinen et al 1998;Reeves et al 2003).…”
Section: Elastic Properties Of the Mt Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…One other factor could also affect twitch contractile characteristics and could explain one part of our results. Indeed, a recent study has observed that musculotendinous stiffness decreases following strength training in elderly individuals and could be due to peripheral but also neural adaptations [44] . If we consider this original result along with the fact that more compliant series elastic components in the muscles tend to decrease twitch force [45] and can also partly cause a slowing of the twitch Ct [46] , we can hypothesize that one part of our results in older men could be attributed to a reduction of the musculotendinous stiffness properties.…”
Section: Muscular Twitch and M-wavementioning
confidence: 99%